A new intelligent self-service express delivery system based on mobile cloud computing and WeChat. (2018) - Zhang, Yongliang; Li, Ling
In order to solve the 'last mile' logistics and distribution problems in express parcel delivery, this paper designs an intelligent system by integrating mobile cloud computing with WeChat to achieve the couriers' self-service parcel picking and delivering as well as customers' self-service parcel sending and receiving. This system is comprised of three parts, namely, express delivery terminals, WeChat public platform and cloud computing servers. The terminal adopts a dual-CPU architecture equipped with Samsung Exynos4412 and STM32F103. The WeChat platform Web-App is built using the web development kit (JS-SDK) within WeChat, which integrates information publishing, online inquiry, interaction and other functions. By using third-party maps and cloud computing servers, this system can mark the real time location of terminals and work out optimal pedestrian navigation routes for customers.